Addition of spironolactone in patients with resistant arterial hypertension (ASPIRANT): a randomized, double-blind, placebo-controlled trial - Václavík, Jan; Sedlák, Richard; Plachy, Martin; Navrátil, Karel; Plásek, Jirí; Jarkovsky, Jirí; Václavík, Tomás; Husár, Roman; Kociánová, Eva; Táborsky, Milos (Hypertension (Dallas, Tex., 2011)
There is currently limited data on which drug should be used to improve blood pressure (BP) control in patients with resistant hypertension. This study was designed to assess the effect of the addition of 25 mg of spironolactone on BP in patients with resistant arterial hypertension. Patients with office systolic BP >140 mm Hg or diastolic BP >90 mm Hg despite treatment with at least 3 antihypertensive drugs, including a diuretic, were enrolled in this double-blind, placebo-controlled, multicenter trial. One hundred seventeen patients were randomly assigned to receive spironolactone (n=59) or a placebo (n=58) as an add-on to their antihypertensive medication, by the method of simple randomization. Analyses were done with 111 patients (55 in the spironolactone and 56 in the placebo groups). At 8 weeks, the primary end points, a difference in mean fall of BP on daytime ambulatory BP monitoring (ABPM), between the groups was -5.4 mm Hg (95%CI -10.0; -0.8) for systolic BP (P=0.024) and -1.0 mm Hg (95% CI -4.0; 2.0) for diastolic BP (P=0.358). The APBM nighttime systolic, 24-hour ABPM systolic, and office systolic BP values were significantly decreased by spironolactone (difference of -8.6, -6.6, and -6.5 mm Hg; P=0=0.011, 0.004, and 0.011 [corrected]), whereas the fall of the respective diastolic BP values was not significant (-3.0, -1.0, and -2.5 mm Hg; P=0.079, 0.405, and 0.079). The adverse events in both groups were comparable. In conclusion, spironolactone is an effective drug for lowering systolic BP in patients with resistant arterial hypertension.
Keywords: Drug Resistance; hypertenze; Female; systola; výsledek terapie; ženské pohlaví; léková rezistence; lidé; dvojitá slepá metoda; Blood Pressure Monitoring, Ambulatory; Treatment Outcome; krevní tlak; Hypertension; Double-Blind Method; Male; Aged; Systole; kombinovaná farmakoterapie; ambulantní monitorování krevního tlaku; Diuretics; diuretika; lidé středního věku; Antihypertensive Agents; senioři; mužské pohlaví; antihypertenziva; Blood Pressure; Spironolactone; spironolakton; Middle Aged; Drug Therapy, Combination; Humans